Upaya Pemberantasan Korupsi: Tantangan Dan Langkah-Langkah Konkret - Muchamad Catur Rizky; Didit Darmawan; Suwito Suwito; Rio Saputra; Novritsar Hasitongan Pakpahan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Corruption in Indonesia is a chronic problem that damages the social and economic structure of the country. This paper explores the history of corruption from feudal times to the modern era, highlighting corrupt practices as part of the culture of government. The government has taken serious steps by establishing anti-corruption regulations and institutions to eradicate corruption that harms society and the state. This research uses the literature study method with a focus on improving governance and increasing transparency as an effort to prevent corruption. Through qualitative analysis, this research evaluates the effectiveness of existing anti-corruption regulations and institutions, as well as understanding the impact of corruption on people's social and economic rights. The results show that the government has taken concrete steps, such as establishing the Corruption Eradication Commission (KPK) and encouraging the use of information technology. However, the fight against corruption is faced with structural, cultural, instrumental and management barriers. Measures to improve governance and increase transparency are key to preventing corruption. Challenges include organized corruption, corrupt practices in the private sector, and non-compliance with regulations. Lack of resources is a constraint, and corruption in complex bureaucratic systems complicates case handling. Improving coordination, transparency, and public participation is needed to overcome these challenges. The government needs to continuously monitor and evaluate the effectiveness of corruption-fighting measures. Regular evaluation, public participation, and human resource capacity building are key to creating a strong and resilient system against corrupt practices. Collective awareness and cooperation between the government, anti-corruption organizations, and society are essential to build an Indonesia that is clean from corruption and just for all its people.